Analysis of Failures and Reliability Model of Farm Tractors (Agricultural Engineering, 2020)
Farm tractors due to the nature of their work are exposed to a substantial risk of failures. The issues of their reliability are unusually significant in the aspect of the time limit of realisation of agricultural works in agrotechnical seasons. Nowadays, tractors provided for agriculture have increasingly complex functional units. The aim of the paper was to analyse reliability of presently produced farm tractors. Three tractor makes were evaluated and the analysis of failures was carried out with regard to functional units. Based on the obtained results, the average time of correct functioning and refreshment times and availability of particular tractor makes were determined. It was stated that the obtained empirical data of the correct functioning time and refreshment time may be well described with exponential functions. Significant differences in the values that determine the average time of correct functioning and duration time of refreshment obtained by tractors of the investigated makes were found. From among particular functional units, electric and hydraulic systems were the most often damaged, regardless the tractor make.